2014
DOI: 10.1373/clinchem.2014.225946
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9): Lessons Learned from Patients with Hypercholesterolemia

Abstract: BACKGROUND:Identification of the proprotein convertase subtilisin/kexin type 9 (PCSK9) as the third gene causing familial hypercholesterolemia (FH) and understanding its complex biology has led to the discovery of a novel class of therapeutic agents.CONTENT: PCSK9 undergoes autocatalytic cleavage in the endoplasmic reticulum and enters the secretory pathway. The PCSK9 gene is under the regulatory control of sterol receptor binding proteins 1 and 2. Statins increase PCSK9 and this may modulate the response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…It was also observed that some hepatic furins cleave and inactivate plasma PCSK9 [40]. Overall, plasma PCSK9 concentrations do not directly reflect PCSK9 biological activity [41]. That could explain the absence of correlation between PCSK9 and apoB-48 concentrations observed in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…It was also observed that some hepatic furins cleave and inactivate plasma PCSK9 [40]. Overall, plasma PCSK9 concentrations do not directly reflect PCSK9 biological activity [41]. That could explain the absence of correlation between PCSK9 and apoB-48 concentrations observed in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…3). PCSK9 is known to modify LDL receptor processing [31]. Its expression in the EGF domain of the LDLR locus is regulated by sterol regulatory element-binding proteins 1a and 2, and it binds to the EGF domain of the cell surface LDL receptor.…”
Section: Critical Interpretation Of the Statement Based On Mendelian mentioning
confidence: 99%
“…The theoretical induction of intestinal tumors by an excessive production of bile acid was not confirmed in practice. Due to the lack of safety evidence during pregnancy, PCSK9 inhibitors are contraindicated in this state [97]. Nevertheless, bococizumab did not affect the embryo-fetal development in an animal study [98].…”
Section: Safety Concernsmentioning
confidence: 99%